Descriptive characteristics of concussions in National Football League games, 2010-2011 to 2013-2014 - Clark, M. D.; Breton, B. M.; Asken, M.; Marshall, S. W. (The American Journal of Sports Medicine, 2017)
Background: Despite a high reported incidence rate of concussion, little is known about the on-field characteristics of injurious head impacts in National Football League (NFL) games. Purpose: To characterize on-field features (location, player position, and time during game) and biomechanical features (anticipation status, closing distance, impact location and type) associated with concussions in NFL games over a 4-season period (2010-2011 to 2013-2014). Study Design: Descriptive epidemiology study. Methods: We analyzed video of a subset of reported, in-game concussions for the 2010-2011 to 2013-2014 seasons. These videos represented a sample of injuries that were diagnosed and reported on the same day and that could be clearly associated with an in-game collision as captured on video. We determined anticipation status, closing distance, impact location on the injured player`s helmet, and impact type (helmet-to-helmet, helmet-to-body, or helmet-to-ground). Associations between these variables were analyzed by use of descriptive statistics and tests of association. Results: A total of 871 diagnosed concussions were reported as occurring during NFL preseason, regular season, and postseason games for the 2010-2011, 2011-2012, 2012-2013, and 2013-2014 seasons. A total of 1324 games were played during this period, giving a concussion incidence rate of 0.658 per game (95% CI, 0.61-0.70). From the video-reviewed subset (n = 429; 49.3%), the majority of injurious impacts occurred with good anticipation (57.3%) and <10 yards of closing distance (59.0%). An association was found between anticipation status and play type (?23 = 27.398, P < .001), largely because injuries occurring on pass plays were more likely to be poorly anticipated than injuries during run plays (43.0% vs 21.4%; 21